Analysis of Factors that Influence Students' Decisions in Choosing a State Vocational High School - Hidayanti, Erielia Rohmatul; Kusumaningrum, Desi Eri; Nurabadi, Ahmad (Journal of Education for Sustainability and Diversity, 2025)
This research is aimed at analyzing the factors that influence students' decisions in choosing a State Vocational High School (SMK) as their further education institution. The factors to be analyzed include socioeconomic conditions, parental support, peer support, self-potential, learning motivation, parenting styles, and students' interests. The research method used is quantitative research using factor analysis as the data analysis technique. Questionnaires as the data collection technique. This research was conducted at all State Vocational High Schools in Malang City with X grade students. The results of the research show that there are four factors that influence students' decisions in choosing a State Vocational High School as their further education institution include student interest factors, parental support and parenting style factors, education and family income factors, and social environmental factors. Based on the significant influence, the dominant influencing factor is the student interest factor.